DETERMINANT ATTITUDE TOWARDS LUXURY BRANDS OF MOBILE SELECTION AMONG POSTGRADUATES AT UNIVERSITY MALAYSIA KELANTAN (International Journal of Creative Future and Heritage (TENIAT), 2017)
Psikologi pengguna terdiri daripada beberapa komponen iaitu persepsi, pengetahuan, sikap, niat, motif dan sebagainya. Penulisan ini difokuskan kepada komponen psikologi sikap pengguna. Tujuan kajian ini adalah untuk mengkaji sikap pelajar-pelajar pascasiswazah (Sesi 2015/2016) UMK terhadap penggunaan telefon bimbit berjenama mewah. Hasil analisis data menunjukkan bahawa keperluan sosial, kesesuaian, bahan dan keperluan untuk keunikan adalah faktor-faktor penting yang mempengaruhi sikap pelajar pascasiswazah terhadap jenama mewah telefon mudah alih. Kertas penyelidikan ini mendapati bahawa keperluan pengalaman memberi kesan negative kepada sikap responden terhadap telefon bimbit berjenama mewah. Faedah utama bagi pengurus, pengamal dan kajian masa depan dalam karya turut digariskan. Consumer psychology has various components such as perceptions, knowledge, attitude, intention, motive and others. This study is done particularly on the components of consumer psychology namely attitude. The purpose of this study is to investigate the consumers’ attitudes of postgraduate students’(2015/2017) towards luxury brands of mobile phone in Universiti Malaysia Kelantan (UMK). Results of the study indicate that social need, materialism, need uniqueness and conformity are important factors that infl uence the postgraduate students’ attitude toward luxury brands of mobile phone. This research fi nds out that experiential need has negatively infl uenced attitudes towards luxury of the mobile phone. Key benefi ts for managers and practitioners and future research are also outlined in the paper.
Keywords: Social need, Materialism, Experiential need, Need of uniqueness, Conformity.